Development and field-installation of a mathematical simulation model in support of irrigation canal management - Baume, J.P.; Sally, Hilmy; Malaterre, P.O.; Rey, J. (International Irrigation Management Institute, 1993)
The management of a manually operated irrigation canal with a number of control structures presents a special set of challenges to the system manager, who is often confronted with the problem of identifying and implementing a coordinated operational strategy to meet water delivery targets in the absence of adequate and reliable information on how the system is functioning. The development of a microcomputer-based mathematical flow simulation model of the Kirindi Oya Right Bank Main Canal is the first phase in IIMI's efforts to provide canal managers with an innovative decision-support tool to help them meet these challenges. This research project was also the beginning of a fruitful, mutually rewarding and lasting relationship between the International Irrigation Management Institute (11MI) and the Centre National du Machinisme Agricole, du Genie Rural, des Eaux et. des Forets (CEMAGREF). This research paper, co-authored by staff members of both institutions, is yet another outcome of this excellent, collaborative relationship.